Effect of Carrageenan as Edible Coating on Storage of Manilkara Zapota Fruit - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Manilkara zapota fruits which belong to the family Sapotaceae have been widely cultivated in Vietnam. Immature fruits are hard, gummy and rich in tannin (astringent), while the ripe fruits are soft and, juicy, with a sweet taste and an attractive orange color, which makes them a wonderful dessert fruit. The pulp is sweet and melting. They are normally consumed fresh. Manilkara zapota is a climacteric fruit that ripens shortly after harvest. Objective of this study focused on the carrageenan edible coating affected to weight loss, protein, total soluble solid, vitamin A and vitamin C Manilkara zapota fruits. Different concentrations of carrageenan (0%, 0.5%, 1.0%, 1.5%, and 2.0%) were examined. Results demonstrated that Manilkara zapota fruits which were coated with 1.5% carrageenan could prolong Manilkara zapota shelf-life until 15 days of preservation. So the use of carrageenan coating was one promising method to improve stability of Manilkara zapota fruits during storage.Keywords: Manilkara zapota, Carrageenan, Coating, Shelf-life, Preservation, Stability.